2004
DOI: 10.1645/ge-279r
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Echinostoma Caproni (Trematoda: Echinostomatidae) Antigens in Feces and Serum of Experimentally Infected Hamsters and Rats

Abstract: This study reports on the kinetics of antibody production to Echinostoma caproni and the dynamics of antigens in feces and sera in 2 experimental hosts (hamsters and rats) that display different degrees of susceptibility with this echinostome. Echinostoma caproni produced chronic infections in hamsters, whereas rats lost the infection at 49-56 days postinfection (DPI). Hamsters developed higher antibody responses than rats, probably in relation to different intestinal absorptions of worm antigens in each host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Significant levels of IgG were detected from 1 to 2 wpi and the values progressively increased over the course of the infection. In hamsters, the responses were greater but slower than in mice, and positive levels of IgG were observed from 7 wpi (Simonsen et al 1991 ;Toledo et al 2004b) . In contrast, rats developed a weak IgG response against E. caproni and only low levels of IgG were detected from 7 wpi (Toledo et al 2003b(Toledo et al , 2004cSotillo et al 2007) .…”
Section: Antibody Responsesmentioning
confidence: 94%
See 4 more Smart Citations
“…Significant levels of IgG were detected from 1 to 2 wpi and the values progressively increased over the course of the infection. In hamsters, the responses were greater but slower than in mice, and positive levels of IgG were observed from 7 wpi (Simonsen et al 1991 ;Toledo et al 2004b) . In contrast, rats developed a weak IgG response against E. caproni and only low levels of IgG were detected from 7 wpi (Toledo et al 2003b(Toledo et al , 2004cSotillo et al 2007) .…”
Section: Antibody Responsesmentioning
confidence: 94%
“…For each echinostome species, expulsion of primary infections occurs rapidly in a number of rodent species, while in other species chronic infections are developed . The elimination of E. caproni primary infections in rats occurred at 7-8 weeks postinfection (wpi) (Hansen et al 1991 ;Toledo et al 2004a) , whereas worm survival in hamsters showed a persistence of at least 20 wpi (Toledo et al 2004b) , and in mice the longevity of the adult worms reached 23 wpi (Fried and Peoples 2007) . The elimination of E. trivolvis from mice occurs within 2-3 wpi (Weinstein and Fried 1991) , while in hamsters worms survived for up to 123 days postinfection (dpi) (Mabus et al 1988) .…”
Section: Manifestations Of Resistance To Infectionmentioning
confidence: 99%
See 3 more Smart Citations